Design of a Microsoft Access-based inventory accounting information system at Sunur Farma Pharmacy, Palembang - Hania Bintara Putri; Maria; Evada Dewata (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2026)
Abstract—This activity aims to design an accounting information system for inventory management at Pharmacy Sunur Farma Palembang using Microsoft Access. Data collection techniques used include interviews and documentation, with primary data as the main source. The interview results revealedd that Pharmacy Sunur Farma Palembang has not yet implemented a computerized system. The main issue identified is that inventory records are still managed manually, learding to problems such as inaccurate data, delayed reporting, and difficulties in monitoring stock availability. Based on these issues, this report discusses the design of an inventory accounting information system based on Microsoft Access, with the output being a drug stock card. The research methodology involves system requirements analysis, database design, system implementation, and testing. The designed system is expected to improve the accuracy and efficiency of recording incoming and outgoing goods, as well as support the information needs required for the pharmacy's operations.